Zakład lecznictwa uzdrowiskowego. Część 1. Podstawowe pojęcia oraz prawne aspekty organizacji i działalności tego typu zakładów jako podmiotów leczniczych - Jachimowicz-Jankowska, Paulina (Studia Prawa Publicznego, 2020)
A health resort treatment facility is a particular medical entity that performs therapeutic activities because it is located in a health spa resort municipality which has the status of a spa health resort. Only the spa health resort municipality implements its own tasks related to the maintenance of health spa functions, and creates the conditions for this type of health facility to function and to develop the municipal infrastructure in order to meet the needs of people staying in the municipality for spa resort treatment. The basic, but not the sole, purpose of establishing and maintaining a health resort treatment facility is medical activity consisting in providing spa patients with health services performed as part of spa treatment integrated into the health care system. The study focuses on how the definition of this type of facility has evolved in the legislation and the directions of changes that have occurred as a consequence of the change in the legal status, as well as other important terms referring directly to the spa treatment facility. The presentation of its various types and tasks performed by these establishments enables the identification of numerous interpretation problems related to their qualification. Due to the diversified ownership structure of these medical entities, reference is made to their organizational and legal forms, with a demonstration of the possible consequences that result from transforming these establishments into health resort companies. The current epidemic in Poland allows the scope of limitations in the operation of spa treatment facilities to be shown and, consequently, changes in the organization of some types of these facilities.